2017
DOI: 10.1111/1756-185x.13218
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of Kawasaki disease

Abstract: Kawasaki disease (KD) is a complex disorder which affects genetically susceptible infants and children. Several susceptibility genes (e.g., ITPKC, CASP3, CD40 and ORAI) and chromosomal regions have been identified through genome-wide association and genome-wide linkage studies to have association with KD. Knowledge of susceptibility genes involved in the pathogenesis of KD may provide new insights into diagnosis and treatment of this condition. However, there is much that we still do not know about the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 38 publications
0
74
0
Order By: Relevance
“…7,8,[10][11][12][23][24][25]29 The etiology of KD onset is thought to involve gene-environmental interactions 7,37 and patients affected at ages younger or older than the peak age of onset may also have characteristic genetic factors. 37 More recently, an age-stratified genome-wide association study targeting both Korean and Japanese populations suspected a rare non-synonymous SNP (rs4365796) in the lymphoid enhancer binding factor 1 gene to be a susceptibility gene to specifically affect KD patients younger than 6 months of age. 38 Interestingly, Biezeveld et al suggested that polymorphisms in the mannose-binding lectin gene are one of the determinants of age-defined risks of CAAs in KD patients, being protective in infants but potentially harmful in patients aged >1 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,[10][11][12][23][24][25]29 The etiology of KD onset is thought to involve gene-environmental interactions 7,37 and patients affected at ages younger or older than the peak age of onset may also have characteristic genetic factors. 37 More recently, an age-stratified genome-wide association study targeting both Korean and Japanese populations suspected a rare non-synonymous SNP (rs4365796) in the lymphoid enhancer binding factor 1 gene to be a susceptibility gene to specifically affect KD patients younger than 6 months of age. 38 Interestingly, Biezeveld et al suggested that polymorphisms in the mannose-binding lectin gene are one of the determinants of age-defined risks of CAAs in KD patients, being protective in infants but potentially harmful in patients aged >1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of sex-related risks for developing CAAs, as well as the susceptibility to KD, remains unresolved. 7,37 Previous epidemiological studies reported that males were vulnerable in terms of their susceptibility to KD onset [7][8][9]20 and the development of CAAs. 15,[17][18][19][20] More recently found sex-specific genetic variants involved in KD pathogenesis (eg, FCGR2A His167Arg polymorphism) may provide new insight into KD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Various susceptibility genes have been identified to have association with KD. These includes inositol 1,4,5-trisphosphate 3-kinase C (ITPKC), Caspase-3 calcium release-activated calcium modulator 1 (ORAI1), and CD 40 [19][20][21]. Knowledge about these susceptibility genes may provide new insights in etiopathogenesis of KD.…”
Section: Geneticsmentioning
confidence: 99%
“…1 Epidemiologic clues have provided valuable insights into the nature of the disease including the genetic predisposition that underlies susceptibility. 2 The elucidation of the distinct seasonality, the lack of documented person-to-person spread, and the spatiotemporal clustering of cases all suggest a fluctuating exposure that triggers the disease. 3 Clinical features of the illness, including mucosal inflammation of the lips, tongue, and upper airway coupled with cervical lymphadenopathy and hoarseness, all point to a trigger that enters through the nasopharynx.…”
mentioning
confidence: 99%